2014
DOI: 10.1007/s10897-014-9750-3
|View full text |Cite
|
Sign up to set email alerts
|

American BRCA Outcomes and Utilization of Testing (ABOUT) Study: A Pragmatic Research Model that Incorporates Personalized Medicine/Patient‐Centered Outcomes in a Real World Setting

Abstract: Research to date regarding identification and management of hereditary breast and ovarian cancer syndrome (HBOC) in the U.S. has been confined primarily to academic center-based studies with limited patient engagement. To begin to understand and address the current gaps and disparities in delivery of services for the appropriate identification and optimal risk management of individuals with HBOC, we designed and have initiated the American BRCA Outcomes and Utilization of Testing (ABOUT) Study. ABOUT relies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Several other shortcomings have been discussed in the literature, such as disparities in service delivery for the appropriate identification of individuals with HBOC, including a lack of referral protocols, indicating a need for educational interventions for both providers and patients [29, 30]. Cragun et al and others found that higher socioeconomic status, lower income and low physician referrals contribute to disparities in access to genetic services [31, 32], although we could not support the published finding in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Several other shortcomings have been discussed in the literature, such as disparities in service delivery for the appropriate identification of individuals with HBOC, including a lack of referral protocols, indicating a need for educational interventions for both providers and patients [29, 30]. Cragun et al and others found that higher socioeconomic status, lower income and low physician referrals contribute to disparities in access to genetic services [31, 32], although we could not support the published finding in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies confirm that AA women are substantially less likely to undergo BRCA1/2 testing than White women [22,[29][30][31][32][33]. A case-control evaluation of women with family histories of breast or ovarian cancer at a large urban hospital showed that AA women were much less likely to receive genetic counseling than White women [29].…”
Section: Disparities In Testingmentioning
confidence: 99%
“…The mutation status may determine the medical management of patients, including annual screening and prophylactic surgery, and genetic testing for BRCA1 and BRCA2 is routinely performed in women with hereditary breast and ovarian cancer risk. More than 100,000 individuals in the United States undergo BRCA testing annually [ 8 ]. However, since BRCA testing is a costly procedure (the current charge for full gene sequencing is several hundred to thousands of dollars), most genetic counseling programs recommend less expensive targeted screening for specific BRCA1 and BRCA2 mutations rather than full gene testing [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 100,000 individuals in the United States undergo BRCA testing annually [ 8 ]. However, since BRCA testing is a costly procedure (the current charge for full gene sequencing is several hundred to thousands of dollars), most genetic counseling programs recommend less expensive targeted screening for specific BRCA1 and BRCA2 mutations rather than full gene testing [ 8 ].…”
Section: Introductionmentioning
confidence: 99%